USAHA PENINGKATAN KUALITAS LINGKUNGAN HIDUP BERDASAR ANALISIS KELAYAKAN INVESTASI DALAM BELANJA MODAL - Monica Rahardian Ary Helmina; Erdilla Noormulia Raysalefty (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
The study was carried out explain the feasibility of the investment plan for additional garbage truck by Banjarmasin Environmental Service, viewed from the investment criteria assessment namely in the term of technical, social and econimic feasibility. It was a quantitative descriptive study. The data obtained in the form of Budget Execution Document, Local Revenue Receipt Report, Waste Retribution, and direct interview. The analysis technique is: knowing the source of investment funds, creating a forecast of retribution income during the economic age, making a forecast of operating cost over economic age, evaluating investment proposal with technical analysis, social and economic using NPV, IRR, CBA. The result indicated that (1) From the result of technical aspect and social aspects, the government investment investment for additional garbage truck is feasible to implement. (2) Net Present Value (NPV) method with a social discount rate 9% results negative NPV of Rp.-764.123.860. It means that the investment for additional garbage truck is not feasible. (3) The value of Internal Rate of Return (IRR) is not able to be found since the present value of cost is all negative. So, a positive NPV cannot be found. (4) From Cost Benefit Analysis (CBA) method, comparison result between benefit/cost yields a number of 0.49 which means less than 1. Thus, the feasibility analysis of the investment for additional garbage truck is not feasible.